ACS: A Seafloor Drilling System for the Deepsea Methane Hydrate Program Offshore India - M. E. Williamson (International Marine Minerals Society)
A seafloor based robotic drilling system is being developed for the National Institute of Ocean Technology in Chennai, India to support a National initiative for marine methane hydrate research. The system will be capable of core sampling to 150m below the seafloor in 3000m of water under telemetric control of an operator onboard a research vessel at the surface. Unlike previous robotic drilling systems, this unit (designated the ACS) will use wireline methodology to reduce the number of tool handling operations required to complete the borehole (conventional rod drilling requires 2025 tool handling operations to complete a 100m hole, while wireline requires only 48 operations to reach the same depth).